2017
DOI: 10.1021/acssuschemeng.7b03218
|View full text |Cite
|
Sign up to set email alerts
|

Role of Substituents in the Solid Acid-Catalyzed Cleavage of the β-O-4 Linkage in Lignin Models

Abstract: The role of substituents in the acidolysis of several lignin models bearing a β-O-4 linkage was studied through experimental (by using Nafion SAC-13 as a heterogeneous catalyst) and theoretical data (including transition state calculations). An equilibrium involving the protonation of either α-OH or β-OH groups as well as the dehydration of the α-OH protonated form to yield a benzylic carbocation is assumed. Phenylacetaldehyde and phenol derivatives are the major reaction products for a number of lignin models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…The importance of lignin as the biggest sustainable reservoir for aromatic rings, as not only chemical feedstocks but also material precursors, has been acknowledged broadly. Particularly, for chemical feedstocks, versatile methods have been developed, and these included reduction, oxidation, and solvolysis, and pyrolysis . The utilization of the aromatic nature to prepare aromatics from lignin is recognized as a high‐value valorization.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of lignin as the biggest sustainable reservoir for aromatic rings, as not only chemical feedstocks but also material precursors, has been acknowledged broadly. Particularly, for chemical feedstocks, versatile methods have been developed, and these included reduction, oxidation, and solvolysis, and pyrolysis . The utilization of the aromatic nature to prepare aromatics from lignin is recognized as a high‐value valorization.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [22] on the hydrothermal conversion of b-O-4 model compounds, we demonstrated that the methoxy groups on the phenyl rings significantly increase the rate of conversion of the substrates. To gether with acidolysis studies by the groups of Pelzer [20] and Salvatella, [32] this work demonstrated the importance of substituent effects on the reactivity of lignin linkages. Hence, to accurately understand the reaction pathways and mechanisms of lignins, one should use model compounds with substituents that confer reactivity that is more consistent with that of the structure of real lignin.…”
mentioning
confidence: 83%
“…For 5 b with Bi(OTf) 3 , Al(OTf) 3 , Hf(OTf) 4 or Cu(OTf) 2 , the same reversal of selectivity was seen as with Fe(OTf) 3 with 7 being the dominant product (Table , entries 3–6). When Cu(OTf) 2 was used, a third product was identified (diastereomeric mixture 8 ; Table , entry 6, and Figure S2) . In all the reactions and especially when triflic acid or Fe(OTf) 3 were used (Table , entries 7 and 2), the C 2 acetal 6 was still formed from 5 b .…”
Section: Figurementioning
confidence: 97%
“…Scheme1.Overview of study on lignin models 5a-h. [8] In all the reactions and especially when triflic acid or Fe(OTf) 3 were used (Table 1, entries 7a nd 2), the C 2 acetal 6 was still formed from 5b.O ne possible explanation was that hydrolysis or transesterification with EG of the g-esteri n5b had occurred, reopening the C 2 pathway.W hen the reaction of 5b with TfOH was repeated at twofold dilution (c.f. Ta ble 1, entries 7a nd 8), full conversion of 5b was still observed but the 7/6 ratio increased to 1.7 ( Figure S3), potentially consistent with adecreased conversion of 5b into 5a.…”
mentioning
confidence: 99%